2013
DOI: 10.1002/srin.201300030
|View full text |Cite
|
Sign up to set email alerts
|

Transient Inclusion Evolution during RH Degassing

Abstract: Inclusion morphology, composition and number at different times of RH vacuum treatment were investigated on API‐X70 pipeline steel with ASPEX. It is found that the inclusions are mainly globular CaO–Al2O3–MgO. The inclusion number decreases with time during RH treatment and the removal ratio can reach 72% after 28 min treatment. The initial number of inclusion plays a vital role in final inclusion number, so efforts must be made to eliminate the inclusion before RH treatment to get a highly clean steel. Non‐li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Zhou et al 41) considered the generation of liquid film is mainly related to the wettability of inclusions. Yoshioka et al 118) and Wang et al 130,131) also support that the wettability of inclusions influences their separation behaviors. Table 6 lists the contact angle between oxide inclusions and liquid steel.…”
Section: Separation Of Spinel Inclusions At Steel-slag Interfacementioning
confidence: 86%
See 2 more Smart Citations
“…Zhou et al 41) considered the generation of liquid film is mainly related to the wettability of inclusions. Yoshioka et al 118) and Wang et al 130,131) also support that the wettability of inclusions influences their separation behaviors. Table 6 lists the contact angle between oxide inclusions and liquid steel.…”
Section: Separation Of Spinel Inclusions At Steel-slag Interfacementioning
confidence: 86%
“…Reis et al 129) pointed out that the removal efficiency of inclusions was closely related to the fraction of solid inclusions. Wang et al [130][131][132] also found that solid inclusions are easier to be removed during RH treatment in contrast to liquid inclusions.…”
Section: Separation Of Spinel Inclusions At Steel-slag Interfacementioning
confidence: 98%
See 1 more Smart Citation
“…The secondary refining process is considered to be the main place for the removal of inclusions in molten steel, and the percentage of inclusions removed accounts for more than 70% [34]. Recently, to improve the cleanliness of molten steel, reducing the number of endogenous inclusions, improving the removal efficiency of inclusions and lessening the external inclusions caused by the reoxidation are dominant ways during the RH refining process.…”
Section: Influence Of Process Parameters On the Cleanliness Of Molten...mentioning
confidence: 99%
“…The disadvantage is that the dissolution takes a long time. Aspex adopts the integrated design of electron microscope and energy spectrum, controls the electron microscope and energy spectrum to realize automatic scanning of inclusions and synchronous analysis of chemical components [12]. The sample preparation and the observation surface of Aspex are the same as that of the metallographic observation method and thus also have the same disadvantages as that of the metallographic observation method.…”
Section: Introductionmentioning
confidence: 99%